How do you write two functions for which (f*g)(x)=2x^2+11x-6?

3 Answers
Nov 24, 2016

See below.

Explanation:

The trivial response is to define g(x) = x and f(x)=2x^2+11x-6 then

(f@g)(x)=2x^2+11x-6

You can also proceed in a more general way making

g(x) = a x + b and
f(x) = x^2+x + c and then

(f@g)(x)=a^2x^2+a(1+2b)x+b+b^2+c and then making an equivalence of coefficients

{(2 - a^2=0),(11 - a(1 + 2 b)=0),(6 + b + b^2 + c=0):}

and solving for a,b,c giving

a = sqrt[2], b = 1/4 (11 sqrt[2]-2), c = -167/8 or

g(x)= sqrt[2] x+1/4 (11 sqrt[2]-2)
f(x)=x^2+x-167/8

Nov 24, 2016

f(x)=(x^2-169)/8 and g(x)=4x+11

Explanation:

Another interesting way we could think about this is to complete the square.

2x^2+11x-6=2(x^2+11/2x)-6

color(white)(2x^2+11x-6)=2(x^2+11/2x+121/16)-6-121/8

color(white)(2x^2+11x-6)=2(x+11/4)^2-169/8

So, we can see that our "inner function" is x+11/4 and the outer function would be 2x^2-169/8.

So if f(x)=2x^2-169/8 and g(x)=x+11/4 then (f@g)(x)=2x^2+11x-6.

We can come up with another by just simplifying the function we already had.

2(x+11/4)^2-169/8=2((4x+11)/4)^2-169/8

color(white)(2(x+11/4)^2-169/8)=1/8(4x+11)^2-169/8

So we can write that for f(x)=1/8x^2-169/8=(x^2-169)/8 and g(x)=4x+11, then (f@g)(x)=2x^2+11x-6.

Nov 25, 2016

f(x)=2x^2+3x-20 and g(x)=x+2

Explanation:

Another method would be to factor first.

2x^2+11x-6=2x^2+12x-x-6

color(white)(2x^2+11x-6)=(2x-1)(x+6)

Choose some arbitrary factor, for example, x+2. We can express each individual factor in terms of x+2.

color(white)(2x^2+11x-6)=(2(x+2)-5)((x+2)+4)

If we let x+2=u this becomes

color(white)(2x^2+11x-6)=(2u-5)(u+4)

color(white)(2x^2+11x-6)=2u^2+3u-20

So we can say that if f(x)=2x^2+3x-20 and g(x)=x+2, then (f@g)(x)=2x^2+11x-6.